Spintronics X 2017
DOI: 10.1117/12.2274750
|View full text |Cite
|
Sign up to set email alerts
|

Non-equilibrium magnetic effects at interfaces for ultrafast dynamics (Conference Presentation)

Abstract: Non-equilibrium magnetic effects at interfaces for ultrafast dynamics Representing the future of spintronics, femtosecond spin current (SC) pulses constitute a versatile tool to transfer spin and control magnetization on the ultrafast timescale. It is therefore of paramount importance to understand the kinetics of these pulses and the fundamentals of their interaction with magnetized media. In our work, we demonstrate the key role of interfaces for the SC dynamics in Fe/Au/Fe multilayers. In particular, we arg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…During the last decades, these techniques have been advanced in the context of ultrafast demagnetization dynamics [11,12] that paved the way for the description of new physics at the sub-picosecond regime. High-frequency resonant modes of exchange magnons have been measured with ultrafast time-resolved optical techniques [8,10,13]. Therefore, the validity of the LLG equations has been confirmed down to the picosecond time scale and below.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…During the last decades, these techniques have been advanced in the context of ultrafast demagnetization dynamics [11,12] that paved the way for the description of new physics at the sub-picosecond regime. High-frequency resonant modes of exchange magnons have been measured with ultrafast time-resolved optical techniques [8,10,13]. Therefore, the validity of the LLG equations has been confirmed down to the picosecond time scale and below.…”
Section: Introductionmentioning
confidence: 90%
“…Since then, the so-called Landau-Lifshitz-Gilbert (LLG) equation is known to give an excellent description of the dynamics of the magnetization, including ferromagnetic resonance (FMR) and magnetostatic waves [4,5], as well as the magnetization reversal [6,7]. Ferromagnetic resonance and time-resolved magnetization measurements allow its spatially homogeneous precession (k = 0) but also non-uniform modes of the magnetization precession (k = 0, where k is the wave vector of spin waves) to be measured [8][9][10]. During the last decades, these techniques have been advanced in the context of ultrafast demagnetization dynamics [11,12] that paved the way for the description of new physics at the sub-picosecond regime.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, it was experimentally shown that basic spintronic effects not only operate in the DC and GHz regime, but also in the ultrafast (THz) regime. 1 Examples include the spin-Hall effect (SHE) and its inverse (ISHE) 2,3 in metals with strong spin-orbit coupling, spin pumping and spin-transfer torque (STT) 4,5 at interfaces of non-magnetic metals and ferromagnets, and magnon generation. 6 Furthermore, ultrafast versions of the spin-Seebeck effect 7,8 and the giant magnetoresistance in ferromagnet|normal-metal multilayers 9 were demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…1 (a), are prepared [32]. The measurements of the THz-frequency spin dynamics are based on the optical pump-probe technique developed in [33], and used in [34,35]. The magnetization dynamics in a Fe wedge (collector) is excited by an ultrashort spin current pulse generated in the Fe emitter by a laser pump pulse.…”
mentioning
confidence: 99%
“…Only the first three modes are observable above the noise floor of the experiment. Of cause there are other limiting effects reducing the observed amplitude of high frequency PSSW modes namely the overlap between the spatial profile of the PSSW with that of interface-confined STT [35], the frequency spectrum of the spin current pulse, and the MOKE sensitivity depending on the PSSW mode number, as discussed in [31]. All of these factors can be modelled in detail, however this discussion is beyond the scope of this paper.…”
mentioning
confidence: 99%